1983
DOI: 10.1002/ar.1092060307
|View full text |Cite
|
Sign up to set email alerts
|

Envirnmental conditions prerequisite for complete limb regeneration in the postmetamorphic adult land‐phase salamander, Ambystoma

Abstract: Historically, postmetamorphic adult land-phase salamanders have been shown to exhibit minimal to nonexistent limb regeneration. Hence, it has been generally accepted that these forms have lost the intrinsic capacity to regenerate a limb. Due to the experimental protocols used, an alternate explanation is also possible: that this intrinsic capacity cannot be expressed when the salamanders are maintained under adverse laboratory environmental conditions. Therefore, this study addresses two questions: 1) What are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 12 publications
1
41
1
Order By: Relevance
“…Two hundred postmetamorphic adult Ambystoma (annulaturn, maculatum, texanum, and tigranurn) were obtained and housed as reported by Young et al (1983a). The salamanders were allowed to acclimate to these conditions for a period of 6 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hundred postmetamorphic adult Ambystoma (annulaturn, maculatum, texanum, and tigranurn) were obtained and housed as reported by Young et al (1983a). The salamanders were allowed to acclimate to these conditions for a period of 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining salamanders were also fixed for gross dissection. The 160 salamanders in the experimental population, consisting of 40 postmetamorphic adults of each species, were treated as follows: Four salamanders per species per putation of the forearm on one side while the opposite side underwent a sham operation and was designated as a control (Young et al, 1983a).…”
Section: Methodsmentioning
confidence: 99%
“…However, in reality, regenerative potential varies among species of a taxonomic group and probably also among individuals of a population. For example, some related adult salamanders of the genus Ambystoma regenerate limbs very quickly while others regenerate slowly [2], [3]. It has also been reported that some salamanders lose the ability to regenerate later in life, especially after metamorphosis, and that a few species have lost the ability to regenerate limbs altogether [4].…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable regenerative capacity of salamanders has been known since first reported by Spallanzani in 1769 [77]. Regenerative studies have included phylogenetic, seasonal, and environmental analysis of limb regeneration [77][79]. Environmental factors that have been considered to affect regeneration include temperature, diet, photoperiod, parasitism, infection, and quality of terrestrial and aquatic microhabitats [79].…”
Section: Discussionmentioning
confidence: 99%
“…Regenerative studies have included phylogenetic, seasonal, and environmental analysis of limb regeneration [77][79]. Environmental factors that have been considered to affect regeneration include temperature, diet, photoperiod, parasitism, infection, and quality of terrestrial and aquatic microhabitats [79]. Human-induced alterations to the NFWR and surrounding landscape have resulted in changes to the physical-chemical properties of the NFWR, including nutrient-loading, introduction of estrogenic chemical levels, algal blooms, and a microbial content deemed unsafe for full body contact by state and federal agencies [43], [80], [81].…”
Section: Discussionmentioning
confidence: 99%